The role of PGRP proteins in innate immunity pathways in the malaria vector Anopheles gambiae - Meister, Stephan (2006)
Innate immunity is the first line of defense against invading microorganisms and provides clues to adaptive immunity for the development of memory for subsequent infections. Insects, similar to other invertebrates, do not have adaptive immunity and thus rely on their innate immune system to combat infections. We have analyzed the role of the peptidoglycan (PGN) receptor protein (PGRP) family and other components of innate immune signaling pathways in the immune defense of the mosquito Anopheles gambiae, the main vector of human malaria in sub-Saharan Africa. The PGRP gene family consists of seven genes with ten PGRP domains. We have shown that from all PGRP genes only PGRPLC has a role in the resistance to bacterial infections of both Gram types. In our experiments we have used the Gram-positive bacterium Staphylococcus aureus and the Gram-negative bacterium Escherichia coli. The PGRPLC gene encodes at least three isoforms that derive from infection-driven alternative splicing of a pool of immature transcripts. Each isoform contains a different PGRP domain, encoded by three exons that all contribute equally to the PGN binding pocket. Structural modeling of the PGRPLC isoforms revealed a potential for all isoforms to bind both types of PGN, the Lys-type, which is mostly found in Gram-positive bacteria and the DAP-type, mostly found in Gram-negative bacteria. The isoform PGRPLC3 seems to be the most important in the defense against both bacteria species, although PGRPLC1 also has a crucial role in the defense against S. aureus. Bacterial defense is mediated by the NF-κB transcription factor REL2, which is the ortholog of the Drosophila Relish. The REL2 gene also encodes two protein isoforms: REL2-S, which only has the NF-κB domain, and REL2-F, which carries an I-κB inhibitory domain and a death domain in addition. REL2-F functions together with the receptor adaptor protein IMD to deal with S. aureus infections, whereas REL2-S has a role in the defense against E. coli. The PGRPLC/IMD/REL2-F pathway (IMD) is also partly responsible for the losses of Plasmodium berghei, which can be observed during the first stages of malaria infection of A. gambiae. P. berghei is a rodent malaria parasite, which has been used as a model in our studies. Whether the pathway is able to recognize the malaria parasite through PGRPLC or another associated receptor is still unclear. Another possibility is that the pathway is activated by the proliferation of commensal bacteria in the mosquito gut following a blood meal. However, we have shown that more than one of the three main isoforms of PGRPLC are required for the reaction to P. berghei. Other PGRP genes, which have been proven to play a role during infection with P. berghei, are PGRPLA2, which also mediates parasite killing, and the almost identical and thus hardly indistinguishable PGRPS2 and S3, which appear to inhibit parasite killing. This is possibly achieved by negative regulation of the IMD pathway through sequestration of PGN, which derives from the commensal bacteria and constitutively activates the pathway. We have shown that REL1, the second NF-κB transcription factor of A. gambiae, which is orthologous to the Drosophila Dorsal (Dif does not exist in Anopheles), is not involved in the mosquito resistance to bacterial infections. This fact provides additional evidence that the REL2-associated pathways are of utmost importance in the A. gambiae defense to bacteria. In addition, REL1 has no role in the documented P. berghei killing. However, silencing of the REL1 inhibitor CACT (the ortholog of the Drosophila Cactus) during a parasite infection leads to a very strong refractoriness phenotype: most of the midgut-invading ookinetes are eliminated (presumably by lysis) and the remaining of the ookinetes are melanized. We thus assume that under wild-type infection conditions the parasite is either evading recognition by the REL1-associated receptors or actively modulating activation of REL1. In conclusion, the data reported in this PhD thesis suggest significant divergence of immune signaling between the mosquito A. gambiae and the fruit fly D. melanogaster. The observed differences most likely reflect their different lifestyles and, consequently, different infectious agents, which the two insects encountered during their evolutionary lifetimes. In mosquitoes one of these agents is the malaria parasite.
Keywords: Hochschulschrift